Fermentation Process Optimization and Aroma Components Analysis of Red Pear Wine with Candy Sugar - Zihao YAN; Qingfang MENG; Jiangkui CHEN; Jiayi SUN (Shipin gongye ke-ji, 2022)
In order to obtain the best fermentation technology of red pear wine with candy sugar, improve the value of the red pear and promote its industrialization. Choose the red pear of Weixian as major material to produce rock sugar red pear wine. On the base of single-factor experiments, the fermentation technology of red pear wine with candy sugar was optimized by orthogonal test and the flavor ingredients of the optimized red pear wine with candy sugar were analyzed. The results indicated that the best fermentation conditions were as follows: The fermentation temperature was 19 ℃, the initial sugar content was 18°Brix, the amount of yeast addition was 0.06%, the initial pH was 4.8, the amount of potassium pyrosulfite addition was 160 mg/L and the fermentation times were 7 days. Under this condition, the alcohol content was 10.1%vol±0.23%vol, the sugar content was 6.17°Brix±0.14°Brix, the total acids were 4.8±0.13 g/L, the sensory score was 88.9±0.57 scores, and the comprehensive value was 79.1±0.79 scores. The aroma components were analyzed qualitatively by the gas chromatography-mass spectrometry (GC-MS). A total of 36 volatile substances were detected, of which the relative content of esters was the highest, accounting for 60.2%, alcohols accounted for 18.31%, acids accounted for 13.32%, aldehydes, ketones, and phenols accounted for 3.63%, 1.75% and 0.78%, respectively.